Seeking abortion medications online: experiences from a mystery client study in Colombia - Daniel Arango Arango; Alice F Cartwright; Ava Braccia; Ann Moore; Maria M Vivas (BMJ Open, 2025)
Objectives While Colombians gained broad legal access to abortion in 2022, people still lack knowledge about its availability and face variable quality of care at health facilities. This study sought to understand whether online sellers provide the instructions and medication dosages necessary for effective medication abortions.Design The study design involved mystery clients contacting sellers identified across websites and social media platforms (Facebook, Instagram, and TikTok) to purchase abortion pills. Unique sellers were contacted with two profiles (first and second trimester pregnancy gestational ages). Mystery clients documented information received on physical effects, complications and how to take the pills from the sellers in a predesigned survey in SurveyCTO.Setting The study was conducted in Colombia from July to September 2023. We documented and described sellers’ conversations with mystery clients and pills received. We identified 161 sellers across platforms, which resulted in 65 unique sellers after deduplication. We attempted to contact each unique seller twice.Results Almost all sellers screened for gestational age using last menstrual period. Bleeding (84.6%) and cramping (66.7%) were the physical effects most commonly mentioned to mystery clients, although pain was mentioned to second trimester clients more often than first (40.5% vs 22.0%). Less than 17% of sellers highlighted possible complications that could require medical attention. Almost 90% of purchases were received (88.9%). All contained manufacturer-branded misoprostol and 77.5% were undamaged aluminium blister packages. While 82.6% of first trimester clients were instructed to take an initial misoprostol dosage in line with Colombia’s Ministry of Health guidelines, all second trimester clients were told to take a dosage exceeding the recommended amount. Although most sellers provided appropriate information on administration routes for the pills, sellers also provided contradictory and unnecessary instructions.Conclusion Online sellers of abortion pills may persist even as legal abortion becomes more widely available in Colombia. While misoprostol was received from many of these sellers, they did not provide sufficient information about potential complications or accurate dosing instructions to second trimester clients. Accurate medication abortion information specific to Colombia should be made more accessible so that people can more easily navigate the new care landscape.